Gradient-temperature hydrothermal fabrication of hierarchical Zn2SnO4 hollow boxes stimulated by thermodynamic phase transformation. Issue 37 (6th September 2016) - Liu, Xiong; Niu, Chaojiang; Meng, Jiashen; Xu, Xiaoming; Wang, Xuanpeng; Wen, Bo; Guo, Ruiting; Mai, Liqiang
Abstract : We report a gradient-temperature hydrothermal method to construct hierarchical Zn2 SnO4 hollow boxes, and the obtained results are based on phase transformation between metastable ZnSnO3 and stable Zn2 SnO4 . Abstract : We develop a facile gradient-temperature hydrothermal method to synthesize hierarchical Zn2 SnO4 hollow boxes based on phase transformation between metastable ZnSnO3 and stable Zn2 SnO4 . This strategy is widely extended to ZnSnO3 microspheres, ZnSn(OH)6 nanocubes and Co-ZIF-67 polyhedrons. When employed as a LIB anode, Zn2 SnO4 hollow boxes exhibit apparently enhanced electrochemical performance.